Pengaruh Intensitas Modal, Leverage, Likuiditas dan Profitabilitas terhadap Agresivitas Pajak - Mufrihatul Awaliyah; Ginanjar Adi Nugraha; Krisnhoe Sukma Danuta (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This purpose of this study was to determine the effect of independent variabels: capital intensity, leverage, liquidity and profitability on the dependent variable namely tax aggressiveness, which is proxied by using CETR in food and beverage sub sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The population in this study were 26 companies and obtained 13 companies using purposive sampling method. The data used is secondary data in the form of financial reports obtained through the website www.idx.co.id and the official website of the related company. The method in this research is panel data regression using Eviews software. The results showed that the capital intensity and profitability variabels had no positive on tax aggressiveness, while the leverage and liquidity variabels have a positive and significant effect on tax aggressiveness.